The rebirth of a station an adaptive reuse and redevelopment of the PNR Paco Station - Tibayan, Joana Mae S.; Luna, Markel Cesar (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The Paco Station, designed by American architect, William Parsons, is a part of PNR's Metro South line which runs from Tutuban to Calamba. It was envisioned to be Manila's Grand Central Station with the aim to extend the city's progress and to link nearby cities north and south, with the capital city of Manila. Sadly, it was a short lived dream as Paco was bombed and greatly damaged during the second World War. Currently, the structure remains unused and abandoned along Quirino avenue, corner Pedro Gil Street. This thesis proposal is a possible solution in preserving the historical structure of Paco station using adaptive reuse and redevelopment of a structure. The old structure would function again, not only as a station, but as a multi functional station serving as an events spaces, admin spaces and commercial spaces. In preserving a historical structure, we must keep in mind that the best way to preserve a building is to keep using it.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Railroads -- Stations; Rail Transportation -- Philippines